2006
DOI: 10.1111/j.1442-2042.2006.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

EDTA‐induced urothelial cell shedding for the treatment of superficial bladder cancer in the mouse

Abstract: Aim:The aim of this study was to determine the effect of intravesical EDTA instillation on the development of intravesically implanted tumor cells in normal mice. Methods: The mouse bladder tumor (MBT-2) model was used in female C3H/eb mice to evaluate the amount of normal urothelial cell shedding, and the degree of tumor growth inhibition following intravesical EDTA instillation in comparison with phosphatebuffered saline (PBS) instillation. Results: At 1 h after instillation, the number of urothelial cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Complete emptying of the bladder before instillation prevents over-distension of the bladder. As expected, increasing the amount of cancer cells reportedly increases the tumour take rate [11][12][13][14]23]. Shapiro et al [24] reported a higher tumour take rate when more cells were used for implantation, which increase from 30% to > 90% when tumour cells used increased from 2.5 × 10 5 to 1 × 10 6 under similar conditions.…”
Section: Implantation Techniquessupporting
confidence: 55%
See 2 more Smart Citations
“…Complete emptying of the bladder before instillation prevents over-distension of the bladder. As expected, increasing the amount of cancer cells reportedly increases the tumour take rate [11][12][13][14]23]. Shapiro et al [24] reported a higher tumour take rate when more cells were used for implantation, which increase from 30% to > 90% when tumour cells used increased from 2.5 × 10 5 to 1 × 10 6 under similar conditions.…”
Section: Implantation Techniquessupporting
confidence: 55%
“…One of the concerns in any orthotopic bladder cancer model is the success rate of tumour implantation. The rate of tumour 'take' with various models is 30% [10] to 100% (Table 1) [4, [11][12][13][14][15][16][17][18][19][20][21][22]. Poor tumour take results in the waste of valuable time and resources, and can affect the interpretation of study results.…”
Section: Orthotopic Bladder Cancer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cytotoxic effect was found only in cells that were in direct contact with a suitably high concentration of chitosan. Such limited toxicity gives chitosan a new and very promising role for both theoretical studies of cell detachment and subsequent regeneration and in clinical application, especially in fighting chronic cystitis (Dalal et al 1994;Mulvey et al 1998Mulvey et al , 2001 and superficial bladder cancers (Nativ et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By removing the layer of umbrella cells, it is highly probable that the majority of bacteria can be cleared from the bladder. Last but not least, induced desquamation has been proposed as a possibility for removing superficial tumours of the urinary bladder (Nativ et al 2006).…”
Section: Discussionmentioning
confidence: 99%